ANALISIS TINGKAT KESEHATAN BANK UMUM PERSERO YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PENDEKATAN RGEC (Universitas Muhammadiyah Palembang, 2023)
Purpose–This study aims t analyze analyze the soundness of state-owned commercial banks listed on ten Indonesian Stock Exchange for the 2020-2022 period using a risk based approach often called RGEC Approach (Risk profile, Good Corporate Govenance, Earning & Capital). Design/methodology– The data used in this study is secondary data obtained from the annual reports of state-owned commercial banks. The method used in thisresearch is a quantitative descriptive method. The data will be analyzed based on criteria set by Bank Indonesia and Financial Service Authority. Findings - Based on the analysis, the result show that in the 2020 – 2022 period, state-owned commercial banks have a good level of soundness or have a healthy rating. This is shown from the Net Performing Loan (NPL), Good Corporate Governance (GCG), Return on Asset (ROA) and Capital Adequacy ratio (CAR) values which are generally in a healthy rating, some of the banks even have a very healthy rating.